2007
DOI: 10.1093/mutage/gem032
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxicity assessment in oncology nurses handling anti-neoplastic drugs

Abstract: Many anti-neoplastic drugs are used globally during chemotherapy in the treatment of cancer. However, occupational exposure to anti-cancer drugs can represent a potential health risk to humans. Investigations on the genotoxicity of these drugs are inconsistent. Further, information on the genotoxic potential of anti-neoplastic drugs in medical personnel from India is not available. Hence, the aim of this study was to carry out genotoxicity monitoring of nurses from the oncology department of a hospital in Sout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
1
7

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(61 citation statements)
references
References 43 publications
4
48
1
7
Order By: Relevance
“…The International Agency for Research on Cancer (IARC) has classified many antineoplastic agents as class 1 human carcinogens (eg, cyclophosphamide, etoposide, busulfan, melfalan), class 2A probably carcinogenic to humans (eg, azacitidine, cisplatin, doxorubicine) or class 2B possibly carcinogenic to humans (bleomycin, dacarbazine, mitoxantrone, mitomycin) (20). Occupational exposure to antineoplastic agents has been shown to result in an increased frequency of total chromosomal aberrations (CATot) in PBL, as documented by a number of studies (2,(21)(22)(23)(24)(25)(26). Interestingly, nurses occupationally exposed to antineoplastic drugs showed an elevated level of not only chromatid-type aberrations (CTA) (induced by most chemical clastogens), but also chromosome-type aberrations (CSA), such as chromosome breaks and dicentric chromosomes, which is typical of radiation exposure (23).…”
Section: Musak Et Almentioning
confidence: 99%
“…The International Agency for Research on Cancer (IARC) has classified many antineoplastic agents as class 1 human carcinogens (eg, cyclophosphamide, etoposide, busulfan, melfalan), class 2A probably carcinogenic to humans (eg, azacitidine, cisplatin, doxorubicine) or class 2B possibly carcinogenic to humans (bleomycin, dacarbazine, mitoxantrone, mitomycin) (20). Occupational exposure to antineoplastic agents has been shown to result in an increased frequency of total chromosomal aberrations (CATot) in PBL, as documented by a number of studies (2,(21)(22)(23)(24)(25)(26). Interestingly, nurses occupationally exposed to antineoplastic drugs showed an elevated level of not only chromatid-type aberrations (CTA) (induced by most chemical clastogens), but also chromosome-type aberrations (CSA), such as chromosome breaks and dicentric chromosomes, which is typical of radiation exposure (23).…”
Section: Musak Et Almentioning
confidence: 99%
“…No statistically significant differences in MN frequencies between hospital personnel occupationally exposed to ANPDs and nonexposed subjects were found in some studies 11−15) , while, in others, higher frequencies of MN were found in either lymphocytes 16−19) or exfoliated buccal cells 15,16) from healthcare workers preparing and/or administering ANPDs. The conclusions of these studies were often contradictory, probably because of uncertainties concerning exposure level 20) or because effective protective measures were differently adopted 21) .…”
mentioning
confidence: 95%
“…12,13 Due to its extensive use in clinics, it possesses occupational exposure to the health care professionals. 14 Fukushima et al reported that many alkylating agents; chemotherapeutic drugs have been found to produce infertility as a result of impaired sperm production. 15 This…”
Section: Discussionmentioning
confidence: 99%